Utilization of Essential Service Package by rural community - Nayan, Shafia Khatun; Begum, Nasreen; Abid, Mumtaz Rahman; Dohja, Maheen; Nazneen, Fazilatun Nessa; Chowdhury, Suraya Ahmed (Northern International Medical College Journal, 2020)
Background: Government has implemented Essential Service Package (ESP) under Health, Nutrition and Population Sector Program (HNPSP) to reach and maintain the highest attainable level of health care to the people of Bangladesh. Objective: To assess the utilization of Essential Service Package by rural community. Methodology: A descriptive, cross-sectional study was carried out during January 2011 to June 2011 on 160 respondents of age 18 years and above.Sample was selected purposively from Nababganj Upazila under Dhaka district. After taking informed consent data were collected by face to face interview using structured questionnaire. Data analysis was done by SPSS version 16. Results: The study revealed that highest number (71.9%) of respondents attended Upazila health Complex (UHC) to utilize ESP services. Among the respondents female (85.6%) were more than male. The lower class (19.4%) and middle class population (46.9%) utilized significantly more than upper class (8.7%).The most of the respondents had primary level of education (31.9%). Utilization of Expanded Programme on Immunization (EPI) (82.9%), Antenatal care (ANC) (16.2%), Family planning (FP) (11.2%), treatment of communicable diseases (40%) and limited curative care (12.5%) were found. Regarding Behavioural change communication (BCC) (41.3%) said that they got health education from the UHC and 58.9% response was negative. Conclusion: The overall utilization of ESP services is good. To utilize the ESP from the existing UHC facilities for the rural community population is needed to be strengthening for achieving the health goals. Northern International Medical College Journal Vol.10 (2) Jan 2019: 377-380